PEMBENTUKAN PERATURAN DAERAH BERBASIS SYARIAH PERSPEKTIF OTONOMI DAERAH DAN HUKUM NASIONAL INDONESIA - Gazali, Gazali (Mu'amalat: Jurnal Kajian Hukum Ekonomi Syariah, 2024)
This research aims to determine the formation of Sharia-based regional regulations in the era of regional autonomy, as well as to find out how the formation of Sharia-based regional regulations is based on Indonesian national law. The research method used is normative or doctrinal research in that the law is conceptualized as what is written in statutory regulations (law in books) or the law is conceptualized as a rule or norm which is a benchmark for human behavior that is considered appropriate. The results of the research found that after the implementation of regional autonomy which was marked by the enactment of Law Number 22 of 1999 replaced by Law Number 32 of 2004 which was also replaced by Law Number 23 of 2014 concerning Regional Government, every Provincial and Regency/City region had very large authority to regulate and manage the region by the characteristics or characteristics of each region. The opportunities provided by the regional autonomy policy are interpreted differently by each region. One of the translations used is to create various Sharia-based Regional Regulations. As well as the formation of Sharia-based regional Regulations is a mandate of applicable laws and regulations, this is confirmed in Article 237 paragraph (2) of Law Number 23 of 2014 concerning Regional Government which states that the stages of forming regional regulations are through planning, drafting, discussing, determination, promulgation. The formation of Sharia-Based Regional Regulations is part of the Indonesian national legal system because the Indonesian national legal system consists of the customary law system, the Islamic legal system which includes (Shariah-Based Regional Regulations), the Western legal system, and the international legal system.